Innovative Strategies for Inclusive and Equitable ASN Talent Management: Insights and Breakthroughs from Indonesia's Public Sector Webinar Series - Puspasari, Azizah; Hapsari, Leonita (Indonesian Association for Public Administration (IAPA), 2024)
The effective implementation of talent management for civil servants (ASN) is critical to achieving a professional and efficient bureaucracy in the Indonesian government. In 2023, the Center for ASN Management Studies at the National Civil Service Agency (LAN) organized a series of twelve webinars titled